2009
DOI: 10.3343/kjlm.2009.29.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Activation of Natural Killer Cells for Cancer Immunotherapy

Abstract: 89Natural killer (NK) cells can kill a wide range of cancer cells and are a promising tool for cell therapy of cancer. NK cells cytotoxicity is regulated by a balance between stimulatory and inhibitory signals. Interleukin-2 is known to increase NK cell cytotoxicity. Although many cytokines have been studied in efforts to induce durable NK cell expansions, most reports indicate a rather modest effect and the requirement for additional stimuli. We found that contact with the K562 myeloid leukemia cell line, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 61 publications
(80 reference statements)
2
53
0
1
Order By: Relevance
“…In order to improve the current treatment modalities, novel approaches to prevent or treat the disease are required urgently. It has been shown that the NK cells of sarcoma patients are as potent as the NK cells of healthy controls in the lysing of the tumor cells (16,17). There is an increasing amount of evidence available concerning the involvement of the immune system and how it may be manipulated in various ways to recognize and kill tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the current treatment modalities, novel approaches to prevent or treat the disease are required urgently. It has been shown that the NK cells of sarcoma patients are as potent as the NK cells of healthy controls in the lysing of the tumor cells (16,17). There is an increasing amount of evidence available concerning the involvement of the immune system and how it may be manipulated in various ways to recognize and kill tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies conducted by Huang et al 26 and Filatenkov et al 27 indicated that radiotherapy damages the immunosuppressive tumor microenvironment and subsequently leads to the recruitment of immune cells such as antigen -presenting cells, T cells, and NK cells, which are crucial in antitumor reactions. 28 Bernstein et al 29 have shown that a single dose of 5 Gy, 10 Gy, or 15 Gy increases the expression of costimulatory molecules and Dosimetric parameters of healthy tissues and selected immune factors The exposure of healthy tissue to X -rays was small (TABLE 1). None of the variables: the SABR schedule, dosimetric parameters such as lung volume exposed to ≥20 Gy (V20 Gy, 20-Gy isodose volume of the lungs), mean lung dose (MLD), esophagus mean dose, as well as other radiotherapy parameters correlated with the immune system parameters, serum CRP levels, or WBC count and ANC.…”
Section: (+) and Cd8(+) Lymphocyte Countmentioning
confidence: 99%
“…In contrast to vaccine therapy or antigen-specific adoptive T-cell therapy, identification of target tumor antigens is not required for NK cell therapy, which can be more universally applied and particularly effective for treating solid tumor malignancies that have lost expression of self-MHC as a mechanism of immune escape from T cells (11,12). However, a major challenge to the broader application of adoptive NK cell therapy has been to develop a method for enriching and expanding the low-frequency NK cells to numbers sufficient for adoptive transfer from the peripheral blood mononuclear cell (PBMC) population (13,14). For T cells, in vitro expansions to more than 1,000-fold can be routinely achieved by T-cell receptor (TCR) triggering using anti-CD3 monoclonal antibody (mAb) in combination with exogenous cytokine in the presence of irradiated feeder cells (15).…”
Section: Introductionmentioning
confidence: 99%